A New Institutional Approach to Innovation Policy. (February 2016) - Davidson, Sinclair; Potts, Jason
Abstract: Modern research and innovation policy is largely based on neoclassical welfare economics, in which the diagnosis of market failure in the production of new information is translated into a case for innovation policy. Both New Institutional and Public Choice economics criticise this approach because it tends to assume that policy interventions are largely costless and produce only benefits. An alternative policy model is proposed that focuses on minimising the social costs of innovation policy through efficient choice of institutions. We review the recently released National Innovation and Science Agenda through this lens.